A Mean-Variance Approach to Portfolio Optimisation for Effective Stock Selection in the Malaysian Stock Market - Muslim, Much Aziz; Dasril, Yosza; Harveend, Mahendran; Muzanah, Rini (Journal of Technology Management and Business, 2024)
Optimization of portfolio selection is very important for overall financial engineering performance. Recent developments in portfolio selection have been developed by many researchers. However, many studies show that prediction with manual models is not enough to achieve highly accurate predictions and prosperous returns. In this paper, a novel portfolio construction approach is developed using the mean-variance (MV) model and maximizing the sharpe ratio for selecting the best portfolio. The approach model is by choosing the best ratio from the comparison between optimal return and annual standard deviation. Experimental data was taken from the Malaysian Stock Exchange from 2020 to 2020, from several securities the ten most active securities were selected. The purpose of this study is to assist investors in verifying the Malaysian stock market so as to reduce risk and maximize returns. The results of the study show that the ratio of the optimal return and the annual standard deviation is 0.711. These results are obtained from a comparison between the optimal return: 33.96% and the annual standard deviation: 47.73%. The proposed model by maximizing the comparison between the optimal return and the annual standard deviation can be used to support portfolio selection decisions. The results showed that the efficiency limits of the selected stocks and optimal portfolio weights could be achieved.